Analysis on the Development of Cold Chain Logistics of Agricultural Products in Guangdong-Hong Kong-Macao Greater Bay Area from the Perspective of the Whole Industrial Chain - Hongxing HUANG; Xiaoke LIU; Weijun LIN (Guangdong nongye kexue, 2023)
Cold chain logistics is of great significance to improving the supply chain resilience of agricultural product industry chain, enhancing the emergency security capability of agricultural products and promoting the high-quality development of agriculture. Promoting the high-quality development of cold chain logistics of agricultural products in Guangdong-Hong Kong-Macao Greater Bay Area(hereinafter referred to as the GBA) is not only an important part of developing modern service industry and improving urban agricultural industry chain, but also an important support for building a high-quality life circle in the GBA. From the perspective of the unique location and industrial space of the GBA, the study analyzes the characteristics, development space and market demand of the cold chain logistics industry of agricultural products in the GBA based on the whole industrial chain. The cold chain logistics industry chain of agricultural products in the GBA is complete, and the number and scale of enterprises are in the forefront of the country. The rise of new models and new formats, such as "cold chain logistics + cross-border e-commerce", "fresh e-commerce + cold chain home distribution", "cold chain logistics + ready-to-cook food", will bring new impetus to the cold chain logistics industry of agricultural products in the GBA. At the same time, the cold chain logistics industry of agricultural products in the GBA is also faced with key problems such as imperfect standard system, low coverage of the whole process of cold chain, low integration of cold chain resources, urban traffic restriction policy, low informatization level, and great difficulty in the whole process of supervision. Under the new situation and pattern, we should fully understand the strategic position of cold chain logistics in the modern agricultural product supply chain, improve the development environment of cold chain logistics industry by optimizing the industrial layout of cold chain logistics, and strive to make up for the outstanding weaknesses of the "first kilometer" and "last kilometer"of agricultural cold chain logistics. At the same time, we should rely on scientific and technological innovation to promote the intelligent, green and standardized development of agricultural cold chain logistics.